Corrigendum: Treatments of Advanced Non‑Small Cell Lung Cancer (NSCLC) in an Italian Center: Drug Utilization and the Treatment Costs of Innovative Drugs - listed], [No authors (Farmeconomia. Health Economics and Therapeutic Pathways, 2019)
There was an error in Discussion section at page 36 in this article by Piantedosi et al. [Farmeconomia. Health economics and therapeutic pathways 2019; 20(1): 27-41; https://doi.org/10.7175/fe.v20i1.1376]. The online version has been corrected on June 5, 2019